Right Ventricular Hypertrophy in Spontaneously Hypertensive Rats (SHR/NHsd) Is Associated with Inter-Individual Variations of the Pulmonary Endothelin System - Langer, Alicia; Schreckenberg, Rolf; Schlüter, Klaus-Dieter; Justus Liebig University Giessen (My University, 2024)
Spontaneously hypertensive rats (SHRs) develop severe hypertension and subsequently left ventricular hypertrophy. Whether they also develop right ventricular hypertrophy is not clear. We analyzed 76 female SHRs (strain SHR/NHsd) and observed severe right ventricular hypertrophy in 7% of these rats (SHR-RVH). Right ventricular hypertrophy did not correlate with the age of the rats and was already seen in one rat at the pre-hypertensive state. The current study investigated the molecular fingerprint of the lung and right ventricle from SHR-RVH and compared this first to SHRs that did develop left but not right ventricular hypertrophy, and second to normotensive rats without hypertrophy. Rats with right ventricular hypertrophy had a decreased expression of the endothelin-B receptor (EDNRB) in the lung, together with an increased protein content of endothelin-1 and an increased expression of ACTA2A. Furthermore, in the right ventricle, a down-regulation of the endothelin-A receptor (EDNRA) was found, consistent with a mild phenotype. The data suggest that in a sub-group of SHR/NHsd rats, low expression of the endothelin clearance receptor (endothelin-B receptor) in the lung triggers an increase in vascular resistance to the right ventricle that then triggers hypertrophy. Our study is the first description of a genetic variant in a defined SHR strain.
Keywords: ddc:610